Correlation of Meat pH and Muscle Fiber Characteristics, Cortisol Level, and Tenascin C Gene Expression in Pigs - Kayan, A.; Koomkrong, N.; Laenoi, W.; Rattanasrisomporn, J. (Tropical Animal Science Journal, 2024)
The effects of meat pH on muscle fiber characteristics, cortisol level, and Tenascin C (TNC) gene expression were examined. The muscle samples (n=100) were randomly collected from the Longissimus thoracis et lumborum (LTL) to determine meat pH at 24 hours (meat pH24h) post-mortem. Muscle samples (five samples per group) with divergent meat pH levels (low versus high) were selected to study muscle fiber characteristics and mRNA expression based on quantitative real-time polymerase chain reaction (qRT-PCR). Blood samples (five samples per group) of the two meat pH levels were taken for serum cortisol analysis. The results showed that there was no significant differences between the groups for the muscle fiber characteristics of total number of fibers, muscle fiber diameter, cross-section area, perimysium thickness, and endomysium thickness. Different meat pH24h values did not affect the cortisol level. The mRNA expression of the TNC gene was significantly (p<0.05) downregulated in the low meat pH24h group compared to the high meat pH24h group. In conclusion, meat pH24h was unrelated to the cortisol level and muscle fiber characteristics. However, the TNC gene might play a role in meat pH24h in pigs.